The impact of business environment institutions on the innovation of Polish small and medium-sized service enterprises - Waldemar Glabiszewski; Dorota Grego-Planer; Katarzyna Liczmańska-Kopcewicz (Economic and Environmental Studies (E&ES), 2018)
This article addresses three fundamental issues. The first issue is Polish small and medium-sized service enterprises, the second - Business Environment Institutions, and the third one - the impact of these institutions on the innovation of the entities in question. The article presents part of the outcome of the research carried out on a group of over two hundred and sixty small and medium-sized service enterprises. The focus of the analysis made was on the intensity of cooperation between these entities and business environment institutions within the area of their innovativeness. The research objective of this article was to assess the impact of business environment institutions on the innovation of Polish small and medium-sized service enterprises. Prior to the commencement of the research we formulated the following research hypothesis - universities are institutions that have the most positive impact on the innovation of micro, small and medium-sized service enterprises. The research questionnaire technique was applied in the survey. The results obtained indicated that the level of cooperation between Polish small and medium-sized enterprises operating in the BEI services sector is very low. This cooperation was found to be usually sporadic or only periodic. Most of the institutions have no influence on the innovativeness of the enterprises surveyed. Only cooperation with entities representing the area of science, research and development transpires to have a significant impact on the level of innovativeness among the respondents.
Keywords: L53; L26; 330; small and medium-sized enterprises; services; business environment institutions; innovativeness